2019
DOI: 10.1021/acs.molpharmaceut.9b00806
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Activated High-Density Materials for Controlled in Vivo Insulin Release

Abstract: In this work we describe the synthesis, characterization and ultimate in-vivo assessment of second generation insulin photoactivated depot (PAD) materials. These are the first to use visible light to stimulate insulin release, and have in-vivo performance that is twenty eight fold improved relative to first generation materials. This improvement is due to two major factors linked to the utilized chemistry: 1) We have incorporated the coumarin photocleavable group, which increases the photo-release wavelength i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Insulin is a hormone, which regulates blood sugar, advised to diabetic patients, and it also undergoes degradation in the presence of gastric enzymes and acids due to destruction of disulfide bonds. pH-responsive carriers offer excellent potential as oral therapeutic systems by enhancing the stability of insulin delivery in stomach and achieving controlled release in intestines. This motivates the development of an oral insulin transport carrier to improve its bioavailability, and various studies have been reported. Considering the advantages of natural materials, researchers are looking for nontoxic, biocompatible, biorenewable, and low-cost natural materials to replace synthetics.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin is a hormone, which regulates blood sugar, advised to diabetic patients, and it also undergoes degradation in the presence of gastric enzymes and acids due to destruction of disulfide bonds. pH-responsive carriers offer excellent potential as oral therapeutic systems by enhancing the stability of insulin delivery in stomach and achieving controlled release in intestines. This motivates the development of an oral insulin transport carrier to improve its bioavailability, and various studies have been reported. Considering the advantages of natural materials, researchers are looking for nontoxic, biocompatible, biorenewable, and low-cost natural materials to replace synthetics.…”
Section: Introductionmentioning
confidence: 99%
“…These species include polymers, nonpolar small molecules, and isoelectric point shifting moieties. The resultant conjugates have minimal solubility, but upon irradiation release native active insulin which can ultimately be absorbed into systemic circulation from the depot site. We have demonstrated the efficacy of this approach both in vitro and in vivo. , The aim of such materials is to allow for the continuously variable release of insulin using light in response to continuously varying blood glucose signals. The combination of continuously variable insulin release and continuous blood glucose information (provided by a continuous blood glucose monitor or CGM) are the central elements of an artificial pancreas (AP). Currently, AP systems exclusively use insulin pumps for delivery.…”
mentioning
confidence: 99%
“…We have demonstrated the efficacy of this approach both in vitro and in vivo. 6,7 The aim of such materials is to allow for the continuously variable release of insulin using light in response to continuously varying blood glucose signals.…”
mentioning
confidence: 99%
“…Photocages are useful in studies that require the spatial and temporal control that can be provided by pulsed light irradiation. These include biological investigations of short-lived species, small molecules, and signaling agents; 1, 2 targeted phototherapeutics; 3,4 and microarray synthesis. [5][6][7][8] Visible light absorbing photocages have been an exciting new development as they allow for less toxic visible light irradiation in biological studies.…”
mentioning
confidence: 99%
“…[5][6][7][8] Visible light absorbing photocages have been an exciting new development as they allow for less toxic visible light irradiation in biological studies. 1,4,[9][10][11] In particular, our group along with others have developed BODIPY photocages which can release leaving groups from the meso position after activation with single photons of green to near IR light. [12][13][14][15][16][17][18] Many biological targets (e.g.…”
mentioning
confidence: 99%